PENGGUNAAN GAYA BAHASA METAFORA DALAM NOVEL TULISAN SASTRA KARYA TENDERLOVA - Rapika, Tri Hana; Amral, Sainil; Rofii, Afif (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2024)
Metaphor is one of the language styles often used in literary works to beautify and enrich the meaning. The proper use of metaphors can make literary works more interesting and easily understood by readers. This study aims to describe the character of the protagonist in the novel Ganjil Genap by Almira Bastari. This research is a qualitative descriptive research. The data in this study are in the form of sentence quotations in which there are characters of the protagonist Gala in the novel Ganjil Genap by Almira Bastari. The approach that the author uses in this research is a structural approach. The results of this study can be concluded that there are findings in the form of quotations related to 4 aspects of metaphorical language style in the novel Tulisan Sastra by Tenderlova. The four aspects are (1) anthropomorphic, (2) animalistic, (3) abstract and (4) synesthetic. From these four aspects, 51 quotations were found about the form of metaphorical language style. The most dominant quotation found in the novel Tulisan Sastra by Tenderlova is the anthropomorphic metaphor as many as 18 quotations, and the least found is the animalistic metaphor as many as 9 quotations. This research is expected to make a scientific contribution to the field of linguistics, especially in the field of pragmatics. The results of this study are expected to help readers to understand the deeper meaning of the novel "Literary Writing" by Tenderlova.